Does Agribusiness Mudharabah Financing Enhance Community Welfare? Initiatives to Achieve Sustainable Development Goals - Huda , Ahsanal; Aini, Nur (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
The primary issue is the disparity in access to agribusiness financing, particularly regarding sharia finance models like mudharabah, which may impede the empowerment of farmers and agricultural entrepreneurs. While mudharabah financing may enhance welfare, issues persist regarding public comprehension of the sharia financing process and the viability of the financed enterprise. An further concern is the reliance on the profit-sharing system, which requires effective management, alongside market uncertainties and natural catastrophes that often jeopardize the security of farmers' income. This research aims to examine the correlation between agricultural mudharabah funding and community welfare in Lampung Province in the context of achieving the Sustainable Development Goals (SDGs). This quantitative investigation used SmartPLS 4.0 statistical software. Primary data were obtained by using a purposive sampling method to pick a sample of respondents. This research used a total of 250 samples. The Likert scale was employed to assess the indications, and data were gathered utilizing Google Forms. The study results indicate that agricultural mudharabah finance significantly influences community wellbeing, particularly for farmers and agribusiness stakeholders. Agribusiness mudharabah finance significantly contributes to the attainment of many Sustainable Development Goals, including poverty alleviation, food security, mitigation of social inequalities, and gender equity.